Q-fever prosthetic valve endocarditis in a patient with SLE and antiphospholipid antibody syndrome - Mayyadah H. Alabdely; Noha Mukhtar; Ahmad Alshaikh; Magid Halim; Shmayel Mohammed; Claudio Pragliola; Ali S. Omrani (Elsevier, 2020)
Q fever prosthetic valve endocarditis in association with antiphospholipid antibody syndrome (APS) in systemic lupus erythematosus (SLE) has not been previously reported. Here, we report a 22-year-old Saudi female diagnosed with SLE and APS. She had mitral valve replacement with bio-prosthesis five years earlier for Libman-Sack endocarditis. She presented with two months' history of fever, cough, palpitations, and progressive shortness of breath. A transthoracic echocardiogram showed a degenerative mitral valve prosthesis with a large mass causing severe obstruction. Open heart surgery revealed multiple masses on the mitral valve. PCR from the resected tissues was positive for Coxiella burnetii DNA. Q fever serology showed phase two IgG 1:2048, phase one IgG 1:512, and IgM 1:1024. The valve was replaced with a bio-prosthesis. She was well at 12 months of follow-up. Keywords: Q fever, Coxiella burnetii, SLE, Antiphospholipid, Endocarditis